The devepment of public school in the Ukraine (second half of the xix th – beginning of the xx th century) - Ємельова, А. П. (Pedagogy of Higher and Secondary Education, 2012)
Еmeleva A. The devepment of public school in the Ukraine (second half of the xix th – beginning of the xx th century). In the article the processes of the development of primary school in the Ukraine (second half of the XIX th – beginning of the XX th century) are under the author’s consideration. The general characteristic of public schools is given, the role of the state, church, zemstvo and community in spreading literacy in the Ukraine is described.